Effects of social facilitation and electronic monitoring on usability - Geaslin, Danica; Harris, Erin J.; Weinberg, Jerry B.; Thomas, Susan L. (2005)
In interface design, typical Usability Testing includes the use of facilitators, observation rooms, and electronic monitoring. Social facilitation theory states that people performing tasks tend to commit more errors when being observed. This study examined aspects of Usability Testing to determine if the effects of social facilitation and electronic monitoring are present. The study examined three aspects: (1) persistent knowledge of being observed, (2) presence of a facilitator, and (3) persistent knowledge of being videotaped. Four groups of subjects were run through a Usability Test. The groups varied in the amount of direct observation and electronic monitoring. In each of the experimental groups significant statistical effects were found in the number of errors the users made. The results suggest ways Usability Testing should be conducted to minimize the effects of social facilitation.